Neutrophilic HGF-MET Signalling Exacerbates Intestinal Inflammation. (17th June 2020) - Stakenborg, Michelle; Verstockt, Bram; Meroni, Elisa; Goverse, Gera; De Simone, Veronica; Verstockt, Sare; Di Matteo, Mario; Czarnewski, Paulo; Villablanca, Eduardo J; Ferrante, Marc; Boeckxstaens, Guy E; Mazzone, Massimiliano; et al.
Abstract: Background and Aims: Ulcerative colitis [UC] is associated with excessive neutrophil infiltration and collateral tissue damage, but the link is not yet completely understood. Since c-MET receptor tyrosine kinase [MET] is required for neutrophil chemoattraction and cytotoxicity in response to its ligand hepatocyte growth factor [HGF], we aimed to identify the function of HGF-MET signalling in neutrophils in UC patients and in mice during intestinal inflammation. Methods: Serum and colonic biopsies from healthy controls and UC patients with active [Mayo endoscopic subscore 2–3] and inactive [Mayo endoscopic subscore 0–1] disease were collected to assess the level of serum and colonic HGF. Disease progression and immune cell infiltration were assessed during dextran sodium sulphate [DSS] colitis in wild-type and MRP8-Cre MET-LoxP mice. Results: Increased mucosal HGF expression was detected in patients with active UC, and in mice during the inflammatory phase of DSS colitis. Similarly, serum HGF was significantly increased in active UC patients and positively correlated with C-reactive protein and blood neutrophil counts. Flow cytometric analysis also demonstrated an upregulation of colonic MET + neutrophils during DSS colitis. Genetic ablation of MET in neutrophils reduced the severity of DSS-induced colitis. Concomitantly, there was a decreased number of TH 17 cells, which could be due to a decreased production of IL-1β by MET-deficient neutrophils. Conclusions: These data highlight the central role of neutrophilic HGF-MET signalling in exacerbating damage during intestinal inflammation. Hence, selective blockade of this pathway in neutrophils could be considered as a novel therapeutic approach in UC.